FIST-Jabatan Pertanian Pahang work on jackfruit disease - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2011)
KUANTAN April 4, 2011. A meeting on management of pest and disease infecting jackfruit variety in Malaysia was held at Jabatan Pertanian Negeri Pahang to overcome the problem of disease infecting a large number of commercial farms in Pahang.